Space Radiation Measurement on the Polar Route onboard the Korean Commercial Flights - Junga Hwang; Jaejin Lee; Kyung-Suk Cho; Ho-Sung Choi; Su-ryun Rho; Il-Hyun Cho (Journal of Astronomy and Space Sciences, 2010)
This study was performed by the policy research project of Ministry of Land, Transport and Maritime Affairs, which title is “Developing safety standards and management of space radiation on the polar route”. In this research, total six experiments were performed using Korean commercial flights (B747). Three of those are on the polar route and the other three are on the north pacific route. Space radiation exposure measured on the polar route is the average 84.7 uSv. The simulation result using CARI-6M program gives 84.9 uSv, which is very similar to measured value. For the departure flight using the north pacific route, the measured space radiation is the average 74.4 uSv. It seems that is not so different to use the polar route or not for the return flight because the higher latitude effect causing the increase of space radiation is compensated by the shortened flight time effect causing decreasing space radiation exposure.